Quasicontinuous Function on Strong Forms of Connected Space - Chander Mohan Bishnoi; Sanjay Mishra (IndoMS, 2023)
Preservation of properties under continuous functions on topological spaces is a very important tool for the classification of topological spaces. However, in some cases the quaiscontinuous functions are more useful than the continuous functions for classifying topological spaces. In this paper, we study preservation of strong forms of connectedness under quasicontinuous function that help to prove the general form of intermediate value theorem.